Potential Efficacy of Midazolam as Second-Line Treatment for Terminal Dyspnea in Patients with Cancer: Secondary Analysis of a Multicenter Prospective Cohort Study - Satoru Miwa; Masanori Mori; Takashi Yamaguchi; Kozue Suzuki; Yoshinobu Matsuda; Ryo Matsunuma; Hiroaki Watanabe; Tomoo Ikari; Yoshihisa Matsumoto; Kengo Imai; Naosuke Yokomichi; Toshihiro Yamauchi; et al. (Palliative Medicine Reports)
Introduction: Opioids are widely used as first-line treatment for dyspnea in terminally-ill patients with advanced cancer (terminal dyspnea), but the merit of second-line treatment for persistent terminal dyspnea despite opioid titration is not clear. Objectives: To explore whether the adjunctive use of low-dose midazolam as second-line treatment for terminal dyspnea is associated with dyspnea relief compared with further opioid titration. Methods: In this preplanned secondary analysis of a multicenter prospective cohort study that consecutively enrolled patients with advanced cancer and terminal dyspnea, we included patients with persistent dyspnea despite opioid titration for whom palliative care physicians added low-dose midazolam (≤10 mg/day) continuously as adjunctive treatment (midazolam group) or titrated opioids further (opioid group). We examined dyspnea intensity (Integrated Palliative care Outcome Scale; IPOS) at the baseline and after six hours. Results: Of the 108 patients enrolled in the main study, 19 exhibited persistent dyspnea despite opioid titration. Four patients were treated with low-dose midazolam, and 15 were treated with further opioid titration. The mean dyspnea IPOS scores decreased from 3.3 [standard error (SE) = 0.2] to 1.3 (0.05) [difference = 2.0 (95% confidence interval [CI] = −0.1 to 3.9); p = 0.07] in the midazolam group and significantly decreased from 2.7 (0.1) to 1.3 (0.2) [difference = 1.4 (95% CI = 0.8 to 2.0); p < 0.001] in the opioid group. No significant between-group differences were noted in the mean IPOS scores at the baseline or after six hours. Treatment-related adverse events were rare. Conclusion: Continuous low-dose midazolam as adjunctive treatment to opioids may serve as second-line treatment for persistent terminal dyspnea. Future randomized-controlled trials are warranted.